A calibrated structural model of the Czech economy - Tibor Hlédik (Bank of Finland, 2003)
The paper presents a structural model framework for a small open economy.The model, based on optimising households and firms, has been calibrated on Czech macroeconomic data in order to develop an analytic framework suitable for analysing key policy questions related to the Czech Republic s anticipated EMU accession.In order to be able to use the model for assessing both pre- and post-accession policy issues, two versions of the model fixed and flexible exchange rate versions were developed.The suitability of the two alternative models for policy analysis was subsequently tested on a series of impulse response exercises.The dynamic responses of the two models to selected shocks and policy experiments are plausible.Hence these results suggest that the presented analytic framework can serve as a good starting point for analysing complex policy issues facing the Czech Republic.
URN:NBN:fi:bof-20140807166
Keywords: E52; E20; E31; F41; 330; monetary policy; monetary union; EMU accession